2021
DOI: 10.1155/2021/4355158
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Preferred Learning Style of Medical and Dental Students Using VARK Questionnaire

Abstract: Students have unique preferences when it comes to knowledge acquisition, information processing, retention in memory, and recall. This study is aimed at examining the preferred learning styles of medical and dental undergraduate students of Pakistan. It is also aimed at investigating the influence of gender, preclinical or clinical academic year, and academic record on the preferred learning style. A descriptive cross-sectional study was conducted in Pakistan. The learning styles of undergraduate students were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
5
19
0
Order By: Relevance
“…Females favoured multi-modal learning, including online availability of presentations and written resources, and online lectures, while males preferred the classroom experience. This is in accordance with previous literature, which showed that female students preferred a multi-modal method of learning in contrast to males, who prefer a single modal learning experience [9,20] and that amongst those students with a single learning preference, the aural (discussions and lectures) are the most favoured [20].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Females favoured multi-modal learning, including online availability of presentations and written resources, and online lectures, while males preferred the classroom experience. This is in accordance with previous literature, which showed that female students preferred a multi-modal method of learning in contrast to males, who prefer a single modal learning experience [9,20] and that amongst those students with a single learning preference, the aural (discussions and lectures) are the most favoured [20].…”
Section: Discussionsupporting
confidence: 92%
“…Unlike previous studies [22] but in concordance with another [9], this study identi ed a difference in learning preferences between preclinical and clinical year students. The preclinical students signi cantly preferred face-to-face lecturing while the clinical year students favoured multi-modal online learning that included pre-recorded lectures, availability of various online resources, followed by tutorial sessions.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Purposive, virtual snowball sampling via WhatsApp and Facebook groups was done [ 29 ]. In Pakistan, MBBS is five years whereas BDS and bachelor of Allied health sciences are four-year degree programs.…”
Section: Methodsmentioning
confidence: 99%